Peran Budaya Lokal Dalam Membangun Agama Yang Sesuai Dengan Kearifan Lokal - Robertus Suraji (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2015)
Religion as a cultural element at one believed by its adherents as a revelation from God. However, it must be accepted that the fact that religion is a divine revelation was revealed to mankind in time and particular culture. The elements of the local culture, however, form the character of a religion. At the same time religions also donate a certain value in culture. Therefore, there is a continuous dialectic between culture and religion that makes religion and culture can continue to grow for a better human life. However, in reality there is not necessarily a good dialogue between religions and cultures. Especially when religion claim that their religion is the only bearer of truth and goodness. As a result not infrequent conflict between religion and culture.